Effect of dietary conjugated linoleic acid (CLA) on lipid composition, metabolism and gene expression in Atlantic salmon (Salmo salar) tissues - Leaver, Michael; Tocher, Douglas R; Obach, Alex; Jensen, Linda; Henderson, R James; Porter, Mark J R; Krey, Grigorios (Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology, 2006)
Dietary conjugated linoleic acid (CLA) affects fat deposition and lipid metabolism in mammals, including livestock. To determine CLA effects in Atlantic salmon (Salmo salar), a major farmed fish species, fish were fed for 12 weeks on diets containing fish oil or fish oil with 2% and 4% CLA supplementation. Fatty acid composition of the tissues showed deposition of CLA with accumulation being 2 to 3 fold higher in muscle than in liver. CLA had no effect on feed conversion efficiency or growth of the fish but there was a decreased lipid content and increased protein content after 4%CLA feeding. Thus, the protein:lipid ratio in whole fish was increased in fish fed 4% CLA and triacylglycerol in liver was decreased. Liver β-oxidation was increased whilst both red muscle β-oxidation capacity and CPT1 activity was decreased by dietary CLA. Liver highly unsaturated fatty acid (HUFA) biosynthetic capacity was increased and the relative proportion of liver HUFA was marginally increased in salmon fed CLA. CLA had no effect on fatty acid Δ6 desaturase mRNA expression, but fatty acid elongase mRNA was increased in liver and intestine. In addition, the relative compositions of unsaturated and monounsaturated fatty acids changed after CLA feeding. CLA had no effect on PPARα or PPARγ expression in liver or intestine, although PPARβ2A expression was reduced in liver at 4% CLA feeding. CLA did not affect hepatic malic enzyme activity. Thus, overall, the effect of dietary CLA was to increase β-oxidation in liver, to reduce levels of total body lipid and liver triacylglycerol, and to affect liver fatty acid composition, with increased elongase expression and HUFA biosynthetic capacity.